Manifestation of kubanga causal connectives in English-Luganda bilingual discourse - Nakijoba, Sarah (Stellenbosch Papers in Linguistics Plus, 2019)
This article presents an overview of the Luganda causal marker kubanga (because) as it occurs in a bilingual Luganda-English spoken discourse. I explore the general structural and functional status of kubanga forms by describing their occurrence in bilingual utterances, explain their context-dependent causal roles and point out their domain specificity. The analysis of data is informed by Myers-Scotton’s (1993, 1995, 2002) Matrix Language-Frame model (MLF), a model which explains the structural configurations of embedded elements within bilingual clauses and Sweetser’s (1990) domain of use model to account for the domain specificity of these forms. Reference will also be made to recent developments in the works on causality (in which the domain model has been reanalysed in terms of Objectivity and Subjectivity). I also make reference to Blakemore’s (2002) Relevance theory-based notion of conceptual-procedural encoding. The findings show that a kubanga form can occur as a single word inserted in an expression which is entirely in English, it can occur in mixed constituents and a kubanga clause can occur as an island. It is evident that kubanga forms operate in four domains (content, epistemic, speech act and metalinguistic) and that they are domain specific. Kubanga forms are positionally mobile and can occupy the initial, medial and final positions in their host clauses.